2018
DOI: 10.1016/j.psychres.2018.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Working Memory Training (CWMT) in adolescents suffering from Attention-Deficit/Hyperactivity Disorder (ADHD): A controlled trial taking into account concomitant medication effects.

Abstract: Although, cognitive working memory training (CWMT) has been reported to enhance working memory functioning in youths with attention-deficit/ hyperactivity disorder (ADHD), few studies take into account the concomitant effects of medication. Sixty adolescents aged from 11 to 15 years were randomly assigned to CWMT treatment, whereas medication was either continued or not introduced (no randomization performed). Results revealed beneficial effects of CWMT on the different components of working memory (WM), namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In particular, several empirical studies have investigated the training effects of computer-based training on children's working memory; some studies found the computer-based training to be effective (Prins et al, 2011;Dunning et al, 2013;Rojas-Barahona et al, 2015; see review by Klingberg, 2010;Morrison and Chein, 2011;Spencer-Smith and Klingberg, 2015), whereas some studies also found the training effect to be insignificant (Wong et al, 2014;de Vries et al, 2015;Melby-Lervag et al, 2016). There were also contradictory results about the transfer effects on inhibition; some studies indicated that computer-based training cannot be transferred to inhibition (Spierer et al, 2013;Ackermann et al, 2018;Hessl et al, 2019), whereas others found the transfer effects to be significant (Blakey and Carroll, 2015;Sanchez-Perez et al, 2018). For flexibility, only one study showed significant transfer effects (Espinet et al, 2013), and most found insignificant results (Egeland et al, 2013;de Vries et al, 2015;Weerdmeester et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several empirical studies have investigated the training effects of computer-based training on children's working memory; some studies found the computer-based training to be effective (Prins et al, 2011;Dunning et al, 2013;Rojas-Barahona et al, 2015; see review by Klingberg, 2010;Morrison and Chein, 2011;Spencer-Smith and Klingberg, 2015), whereas some studies also found the training effect to be insignificant (Wong et al, 2014;de Vries et al, 2015;Melby-Lervag et al, 2016). There were also contradictory results about the transfer effects on inhibition; some studies indicated that computer-based training cannot be transferred to inhibition (Spierer et al, 2013;Ackermann et al, 2018;Hessl et al, 2019), whereas others found the transfer effects to be significant (Blakey and Carroll, 2015;Sanchez-Perez et al, 2018). For flexibility, only one study showed significant transfer effects (Espinet et al, 2013), and most found insignificant results (Egeland et al, 2013;de Vries et al, 2015;Weerdmeester et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gain in WM capacity is what all WM training techniques want to achieve. The digit-span has often been regarded as non-trained measure of short-term memory/WM capacity 9,22,[53][54][55] . Furthermore, the visuo-spatial change detection task, which involves the remembering of spatial locations of objects 56 , is formally similar with n-back task and method of loci on memory environment of spatial domain.…”
mentioning
confidence: 99%
“…Interference control is more compromised in subjects with ADHD than in typically developing individuals [117,118] and visual perception is highly related to higher cognitive processes such as reading comprehension and arithmetic skills [119]. In addition, people with ADHD usually show deficits in tasks that assess visual working memory [120,121], alterations in visuospatial skills related to working memory [122], and in the ability to process spatial information adequately [123]. However, we do not have standardized tests focused on quantification of the deficit, only a qualitative view of the deficit itself.…”
Section: Impulse Control and Cognitive Correlates In Adhd Diagnosementioning
confidence: 99%